Framing Coherence Across EU Policies Towards Integrated Wildfire Risk Management and Nature-Based Solutions - Eduard Plana; Marta Serra; Annick Smeenk; Adrián Regos; Claudia Berchtold; Maria Huertas; Lola Fuentes; Antoni Trasobares; Julie Nicole Vinders; Conceição Colaço; José Antonio Bonet (Fire)
Wildfire risk has been exacerbated across Europe by climate change favoring more damaging and severe wildfire events. This evolving wildfire risk context interacts with a broad landscape of EU policies including those on nature conservation, forestry, bioeconomy or climate and energy, all of which may increase or reduce fire hazard and the level of exposure and vulnerability of the values at risk. Coherently addressed, policies may support wildfire disaster risk management synergistically while reducing potential dysfunctions. This research conducts a content analysis of EU policies and initiatives under the European Green Deal with respect to integrated wildfire risk management and related nature-based solutions. The results show that a consistent EU policy framework to address wildfire risk reduction in a synergic way exists, with no major conflicts in the policy design. Nevertheless, better guidance on fire-smart land management practices and the conceptualization of wildfire-related nature-based solutions may enhance a more coherent policy implementation. Additional suggestions around the legal status of wildfire protection and ‘whole of government’ governance frameworks are discussed. Notably, within the laws, policies and initiatives analyzed, the beneficial side of fire addressed by integrated fire management is either missing or not explicitly mentioned, although it is considered in policy-related supporting guidelines.